A new species of Sedum (Crassulaceae) from northwest Michoacan, Mexico - Costea, Mihai; García-Ruiz, Ignacio (Phytotaxa, 2015)
A new species of Sedum, S. moniliforme (Crassulaceae) is described and illustrated from the Canyon La Gloria, Municipio Jiquilpan, State of Michoacan, Mexico. The closest morphological affinities of this taxon are with Sedum longipes from which it differs through its moniliform or markedly articulate stems with whorled leaves, 3–4 at each node, sepals that are not imbricated at the base, as well as smaller flowers, pollen grains, and sterile rosettes.